OXYGEN ISOTOPE SIGNATURE OF PI REGENERATION FROM ORGANIC COMPOUNDS BY PHOSPHOMONOESTERASES AND PHOTOOXIDATION - Liang Y.; Blake R.E. (My University, 2006)
Phosphomonoesters are an important source of dissolved inorganic orthophosphate (PO4 or Pi), the preferred form of P utilized by microbiota and aquatic plants in marine and freshwater ecosystems. Two enzymes involved in phosphomonoester metabolism and commonly detected in natural waters (alkaline phosphatase and 5?-nucleotidase) have been studied to determine the oxygen isotope signature of Pi-regeneration from phosphomonoesters by enzymatic degradation. Oxygen (O) isotope ratios of water and Pi released from phosphomonoesters during enzyme hydrolysis experiments demonstrate that released Pi incorporates one oxygen atom from water. The isotopic fractionation between this incorporated water O and ambient water O is -30 (?8)? for alkaline phosphatase and -10 (?1)? for 5?-nucleotidase, with very weak dependence on temperature. The result of these enzyme-specific isotopic fractionations at one of the four O sites in PO4 is that the ?18O value of Pi regenerated by 5?-nucleotidase is 5? higher than Pi regenerated by alkaline phosphatase from the same phosphomonoester substrate. The ?18O value of regenerated Pi also reflects inheritance of 75% of O from the phosphomonoester substrate, thus making the ?18O of phosphomonoester-derived Pi a potential tracer of organophosphorous compound sources. Phosphomonoesterase-regenerated Pi has a distinct phosphate oxygen isotope signature that is different and distinguishable from that of biologically recycled and subsequently equilibrated Pi and Pi regenerated from photooxidation of organic matter. The ?18O value of regenerated Pi will correlate positively with the ?18O value of bulk water and the fractionation, ?, between regenerated Pi and water, ?regen Pi-water, should converge toward equilibrium ?Pi-water values with increased biological cycling of Pi.
Keywords: DISSOLVED INORGANIC PHOSPHORUS; ISOTOPIC FRACTIONATION; OXYGEN ISOTOPE; PHOTOOXIDATION